Cost-effectiveness of a nurse-led internet-based vascular risk factor management programme: economic evaluation alongside a randomised controlled clinical trial. Issue 5 (20th May 2015) - Greving, J P; Kaasjager, H A H; Vernooij, J W P; Hovens, M M C; Wierdsma, J; Grandjean, H M H; van der Graaf, Y; de Wit, G A; Visseren, F L J
Abstract : Objective: To assess the cost-effectiveness of an internet-based, nurse-led vascular risk factor management programme in addition to usual care compared with usual care alone in patients with a clinical manifestation of a vascular disease. Design: Cost-effectiveness analysis alongside a randomised controlled trial (the Internet-based vascular Risk factor Intervention and Self-management (IRIS) study). Setting: Multicentre trial in a secondary and tertiary healthcare setting. Participants: 330 patients with a recent clinical manifestation of atherosclerosis in the coronary, cerebral, or peripheral arteries and with ≥2 treatable vascular risk factors not at goal. Intervention: The intervention consisted of a personalised website with an overview and actual status of patients' vascular risk factors, and mail communication with a nurse practitioner via the website for 12 months. The intervention combined self-management support, monitoring of disease control and pharmacotherapy. Main outcome measures: Societal costs, quality-adjusted life-years (QALYs) and incremental cost-effectiveness. Results: Patients experienced equal health benefits, that is, 0.86 vs 0.85 QALY (intervention vs usual care) at 1 year. Adjusting for baseline differences, the incremental QALY difference was −0.014 (95% CI −0.034 to 0.007). The intervention was associated with lower total costs (€4859 vs €5078, difference €219, 95% CI −€2301 to €1825). The probability that the intervention is cost-effective at a threshold value of €20 000/QALY, is 65%. At mean annual cost of €220 per patient, the intervention is relatively cheap. Conclusions: An internet-based, nurse-led intervention in addition to usual care to improve vascular risk factors in patients with a clinical manifestation of a vascular disease does not result in a QALY gain at 1 year, but has a small effect on vascular risk factors and is associated with lower costs. Trial registration number: NCT00785031.